2017
DOI: 10.4172/2155-9899.1000525
|View full text |Cite
|
Sign up to set email alerts
|

Strong Humoral Anti-HLA Immune Response Upon Arbitrarily Chosen Allogeneic Arterial Vessel Grafts

Abstract: Forty-three patients were grafted with forty-four fresh or cryopreserved allogeneic arterial vessels in order to treat infections of synthetic vascular implants as these often lead to sepsis, amputation and death. All the patients were HLA-typed whereas typing results of the post-mortem donors were inquired or genotyped from residuary vessels' segments. 84% of the patients were cured from the underlying infections with a re-infection rate of only 9% attesting this therapeutic procedure a high success rate for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Despite of it, is the use of immunosuppression in patients after clinical arterial allograft implantation not generally accepted by vascular surgeons [ 1 ]. This is probably caused by no acceptance of the antigenicity of arterial allografts by vascular surgeons [ 9 ] and/or a reluctance to use immunosuppressive treatment in patients with ongoing infection [ 31 ]. However, if the immunosuppressive therapy after clinical arterial transplantation is used, the drug most commonly used is cyclosporine A [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite of it, is the use of immunosuppression in patients after clinical arterial allograft implantation not generally accepted by vascular surgeons [ 1 ]. This is probably caused by no acceptance of the antigenicity of arterial allografts by vascular surgeons [ 9 ] and/or a reluctance to use immunosuppressive treatment in patients with ongoing infection [ 31 ]. However, if the immunosuppressive therapy after clinical arterial transplantation is used, the drug most commonly used is cyclosporine A [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the recently published work of Konrad H. et al was clearly demonstrated that cryopreserved arterial allografts used in clinical practice are highly immunogenic in terms of an HLA-directed immune response. This allogeneic immune response does not lead to an acute graft loss but to a chronic vascular degeneration process with clinically apparent thromboses with subsequent medical interventions up to amputations [ 9 ]. The low dose immunosuppression with sirolimus (mammalian target of rapamycine inhibitor) did not show any affective influence on antibody-mediated rejection of these cryopreserved arterial allografts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental and clinical studies revealed strong antigenicity of both cold-stored and cryopreserved allografts, respectively [10,11]. This immunogenicity is responsible for late graft-related complication presented as graft dilatation, rupture or thrombosis [12].…”
Section: Introductionmentioning
confidence: 99%